Parenting Culture(s): Ideal-Parent Beliefs Across 37 Countries. (January 2023) - Lin, Gao-Xian; Mikolajczak, Moïra; Keller, Heidi; Akgun, Ege; Arikan, Gizem; Aunola, Kaisa; Barham, Elizabeth; Besson, Eliane; Blanchard, M. Annelise; Boujut, Emilie; Brianda, Maria Elena; Brytek-Matera, Anna; et al.
What is it to be "an ideal parent"? Does the answer differ across countries and social classes? To answer these questions in a way that minimizes bias and ethnocentrism, we used open-ended questions to explore ideal-parent beliefs among 8, 357 mothers and 3, 517 fathers from 37 countries. Leximancer Semantic Network Analysis was utilized to first determine parenting culture zones (i.e., countries with shared ideal-parent beliefs) and then extract the predominant themes and concepts in each culture zone. The results yielded specific types of ideal-parent beliefs in five parenting culture zones: being "responsible and children/family-focused" for Asian parents, being "responsible and proper demeanor-focused" for African parents, and being "loving and responsible" for Hispanic-Italian parents. Although the most important themes and concepts were the same in the final two zones—being "loving and patient, " there were subtle differences: English-speaking, European Union, and Russian parents emphasized "being caring, " while French-speaking parents valued "listening" or being "present." Ideal-parent beliefs also differed by education levels within culture zones, but no general pattern was discerned across culture zones. These findings suggest that the country in which parents were born cannot fully explain their differences in ideal-parent beliefs and that differences arising from social class or education level cannot be dismissed. Future research should consider how these differences affect the validity of the measurements in question and how they can be incorporated into parenting intervention research within and across cultures.